Imobilização de lipase po diferentes técnicas para obtenção de catalizadores estáveis - Santos, Bruna Leal dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Lipases, also known as glycerol ester hydrolases , are enzymes that belong to the group of serine hydrolases. The mode of action of lipases is very similar to esterase group, performing the hydrolysis of carboxylic esters of glycerides - forming fatty acids and glycerol. The enzymatic bioconversion processes have been widely used in manufacturing, processing and recovery of raw materials. Advances methodology for immobilization of enzyme have allowed the modification of the kinetic properties and stability of these molecules contributing to the increase in the potential applications of the same. The present work is aimed to study different methods of immobilization of lipases in silica supports, and the effects of this procedure to improve the functionality of enzymes. The immobilization methods chosen for the studies were: physical adsorption, covalent bonding and encapsulation process. The process of immobilization of lipase on Celite (by physical adsorption) was optimized taking into account several parameters such as: pH, the enzyme concentration:support and temperature for enzyme activity. Celite was also used as a support for the immobilization of lipase by covalent bond, where best results were obtained with 20% enzymatic activity at 40 ° C and immobilization efficiency of 50%. The celite was activated with 3-aminopropyltriethoxysilane and glutaraldehyde. Finally, we have studied the possibility of encapsulation of lipase using the precusor tetraethylorthosilicate (TEOS). The results of this last methodology were not satisfactory. These results show that to maintain a good catalytic activity depends on the type of immobilization chose (chemical or physical) and the strength of the interaction between the enzyme and support, which can cause structural distortions in the protein, leading maintenance or a decrease in catalytic activity

As lipases, também chamadas de glicerol éster hidrolases, são enzimas que fazem parte do grupo das serina hidrolases, tendo como substrato, triglicerídeos. O modo de ação das lipases assemelha-se ao das esterases, realizando a hidrólise das ligações ésteres-carboxílicas de acilgliceróis, formando ácidos graxos e glicerol. Processos de bioconversão enzimática têm sido bastante utilizados na produção, transformação e valorização de matérias-primas. Avanços na tecnologia enzimática, como a imobilização de enzimas, possibilitaram a modificação das propriedades cinéticas e da estabilidade destas moléculas contribuindo com o aumento no potencial de aplicações das mesmas. O presente trabalho teve por objetivo estudar diferentes métodos de imobilização de lipases em suportes de sílica, bem como os efeitos deste procedimento, visando melhorar a funcionalidade das enzimas e o maior rendimento econômico nos processos industriais. Os métodos de imobilização escolhidos para os estudos foram: adsorção física, ligação covalente e encapsulação. O processo de imobilização de lipase em Celite (adsorção física) foi otimizado levando em conta o pH, porcentagem da concentração enzima:suporte e temperatura ótimos de atividade enzimática. Também se utilizou Celite como suporte para a imobilização de lipase por ligação covalente, onde se obteve os melhores resultados com atividade enzimática 20% a 40 ºC e eficiência de imobilização de 50%. A celite foi ativada com 3-aminopropiltrietoxisilano e glutaraldeído. Por último, foi avaliada a possibilidade de encapsulação da lipase utilizando o precursor tetraetilortossilicato (TEOS). Os resultados obtidos nesta última metodologia não se mostraram satisfatórios. Logo, com os dados obtidos, podemos dizer que uma boa manutenção da atividade catalítica depende do tipo de retenção (química ou física) e da força de interação ...
Keywords: Lipase; Enzimas - Aplicações industriais; Biodiesel; Silica; Enzymes Industrial applications